An Efficient Control Strategy for an Optimal Operation on Clear Water Process Station - Koresh, H. James Deva (Journal of Soft Computing Paradigm, 2021)
Water process stations are very common nowadays, that can be noticed everywhere from a small house to very big industrial area. The main objective of the water process stations are to reduce the hardness of the drinking water. In order to attain such a clear drinking water, the process station will work over several stages like sediment filter, carbon filter and RO membrane. Usually all these stages will be taken into account by the process stations on the feed water irrespective on its hardness measurement. The control strategy imposed in the paper verifies the hardness of the feed water at the very first step to avoid several stages for making the process simpler and faster. In the same way, at the stage of each filtering process huge amount of water will be wasted in the traditional process station. Due to the implementation of an efficient control strategy such wastages can also be minimized in the proposed work. The experimental study performed based on the proposed methodology explores the amount of water saved during the clear water processes as well as the time requirement for processing the feed water.
Keywords: Water process station; clear water process; water filters control